Problems, Stressors and Needs of Children and Adolescents with Cancer - Anna Lewandowska; Barbara Zych; Katalin Papp; Dana Zrubcová; Helena Kadučáková; Mária Šupínová; Serap Ejder Apay; Małgorzata Nagórska (MDPI AG, 2021)
Background: Cancer diseases in children and adolescents are considered to be one of the most serious health problems in the world. It is estimated that about 151,435 cases are diagnosed in children annually. Children with cancer experience many comorbid symptoms related to diagnosis and treatment that can profoundly affect their lives. They experience physical and emotional suffering, which affects their well-being and physical fitness, influencing the prognosis and deteriorating their physical, mental and social functioning. Given the limited data, an attempt was made to assess the problems of the biopsychosocial sphere of need and stressors among children and adolescents treated for cancer. Accurate symptom assessment is essential to ensure high-quality care and effective treatment. Patients and Methods: The qualitative study was conducted in pediatric oncology of hospitals in Poland. Children diagnosed with cancer were invited to participate in the study to assess their problems, stressors and needs. Results: The study included 520 people, where female sex constituted 48% and male 52%. The mean age of the children is 13.2 SD = 2.5. Negative experiences related to the disease are experienced by 82% of children. Among the surveyed children, the most experienced were anxiety (61%). The conducted research shows that as many as 69% of all respondents experienced states that indicate severe depression. The most common somatic problems reported by children were pain (58%). The most dominant areas of life that had a negative impact was body image (85%). Conclusions: Children and adolescents diagnosed with neoplastic disease experience many problems and stressors in every sphere of life, which undoubtedly affects a high level of unmet needs. The main category of needs concerning the challenges faced by children with cancer was psychological and care problems. In the youth group, the needs were mainly related to education and social support.